(untitled) (Journal of Parents and Teachers, 2014)
This article presents a Didactic Unit of technology based on previous knowledge of other years. The Didactic Unit deals with electric current and energy consumption. It also proposes activities and the reasons why this Teaching Unit is motivating and works aspects of the hidden curriculum.